Cross polarization on line-of-sight links in a tropical location: Effects of the variation in canting angle and rain dropsize distributions - Ajewole, O; Kolawole, L; Ajayi, G (IEEE Transactions on Antennas and Propagation, 2020)
International journal IEEE Xplore Vol.47,No8, p.1254 - 1259